The Origin of the Name “Isfandiyar” - Leila Varahram (تاریخ ادبیات)
According to the phonological rules of New Persian, the name "Isfandiyar," which belonged to Gushtasp’s brave son, is an irregular word. This name is derived from Old Iranian "*Spanta.dāta-", and should be pronounced in New Persian as "Ispandiād", as in Middle Persian. However, there is no attestation of this pronunciation in Persian books. This article argues that the proper name "Isfandiyar" is actually a loanword in New Persian, originating from the Azari dialects. A phonological peculiarity of Azari is changing Old Iranian */t/ to /r/ in postvocalic or intervocalic positions. Furthermore, we provide evidence that the Parthian house of Mihran, who claimed that Isfandiyār was one of their ancestors, was the primary source of stories about this hero. As rulers of the Caucasus and Azerbaijan, they delivered the Azari form of his name to the central and eastern Iranian regions in two stages. During the rebellion of Bahram Chobin, they made prominent resemblances between the stories of Isfandiyar and Bahram, which helped to spread the Azari form of his name. In the second stage, the rulers of the Samanid dynasty, who claimed to have descended from Bahram Chobin, extended the Mihranī version of the heroic exploits of Isfandiyar to Khorasan and eastern Iranian regions. As a result, the Azari form of the name became more prevalent, and other forms of this proper name were forgotten, as evidenced by the works of contemporary poets and authors in other regions of Iran.